Establishment of a Southern catfish (Silurus meridionalis) spermatogonial stem cell line capable of sperm production in vitro - Jianeng Li; Changle Zhao; Lei Liu; Shuqing Zheng; Deshou Wang; Changwei Shao; Jing Wei (Aquaculture Reports)
Southern catfish (Silurus meridionalis) is widely distributed in the Yangtze River and its tributaries and is valued for its rapid growth, nutritional content, pleasant taste, absence of intermuscular bone, and disease resistance. However, the species faces challenges in genetic breeding and germ-line preservation due to its late sexual maturity (2–3 years for males and 3–4 years for females) and single spawning cycle. In this study, we successfully established a spermatogonial stem cell line (designated as SC1) derived from the testis of a four-month-old Southern catfish. This cell line has exhibited continuous growth for more than one year, showing significant alkaline phosphatase activity, and maintaining a diploid karyotype. It exhibited expression of germ cell markers, including glial cell-derived neurotrophic factor family receptor alpha-1 (gfrα1) a and b, pou5f3, nanog, and vasa, but no expression of somatic cell markers such as amh, wt1a, and wt1b. Notably, SC1 has shown the ability to differentiate into sperm-like cells in vitro following treatment with retinoic acid (RA) and/or 11-ketotestosterone (KT). Transfection efficiency exceeding 50 % was achieved utilizing microporous membrane electroporation. Furthermore, the sustained proliferation of SC1 was found to depend on a combination of various factors, particularly the extract from Nile tilapia embryos. Collectively, our findings indicate the successful establishment of a Southern catfish spermatogonial stem cell line that exhibits sustained proliferation and sperm production in vitro. This study provides a foundation for generating genome-edited sperm for germ-line transmission in this species and offers a valuable tool for investigating fish spermatogenesis in vitro.